Enhanced Production of Astaxanthin by Co-culture of Paracoccus haeundaensis and Lactic Acid Bacteria - Choi, Seong Seok; Seo, Yong Bae; Nam, Soo-Wan; Kim, Gun-Do (Frontiers in Marine Science, 2021)
This study aimed to determine the increase in astaxanthin production from Paracoccus haeundaensis by optimizing the medium conditions and co-culturing with lactic acid bacteria. In order to select a suitable strain to co-culture with P. haeundaensis, several strains were co-cultured with P. haeundaensis. Lactobacillus fermentum was selected as the optimal strain. Further to optimize the astaxanthin production in the co-culture, various medium conditions were tested and the PMF medium developed in this study was selected as the optimum medium. For the co-culture under optimal conditions, the dried cell mass and astaxanthin concentration were 1.84 ± 0.09 g/L and 821.09 ± 30.98 μg/g-dried cell weight, respectively, which was 2.5 times higher than that of the P. haeundaensis strain in the Luria-Bertani broth medium. In order to confirm the transcription level of the carotenoid biosynthesis genes such as crtE, crtB, crtI, crtY, crtZ and crtW of P. haeundaensis in the co-culture, real-time qPCR was performed. Among the six carotenoid biosynthesis genes, crtI, crtY, and crtZ showed a significant difference in relative RNA levels. The mass culture was performed using a 5 L jar fermenter and the astaxanthin concentration was the same as that at the laboratory scale. These results may be used as reference for co-culture and astaxanthin production in carotenoid biosynthesis microorganisms.